Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2011
DOI: 10.1145/1978942.1979381
|View full text |Cite
|
Sign up to set email alerts
|

African American men constructing computing identity

Abstract: Many young African American males have a passion for video games, but they don't often translate that passion into learning about computing. Part of the problem is that they do not identify with computing as a social norm within their peer group. This disidentification with computing can negatively impact academic performance and limit opportunities for upward mobility. We developed a job training program called Glitch Game Testers in which young African American men are trained to "break open the black box" o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Further analysis showed that an even larger number of manuscripts included an a posteriori focus on gender. Analytical focus on gender in a paper manifested in one or more of the following ways: 1) differentiating subjects for statistical analysis based on gender [57,67,105], 2) restricting the population of study to subjects of one or more specific gender groups [20,32,54], or 3) focus on HCI interventions or innovations around a gendered issue (e.g., pregnancy, gender identity and expression transitions, stereotype bias, etc.) [2,3,9].…”
Section: Gendermentioning
confidence: 99%
“…Further analysis showed that an even larger number of manuscripts included an a posteriori focus on gender. Analytical focus on gender in a paper manifested in one or more of the following ways: 1) differentiating subjects for statistical analysis based on gender [57,67,105], 2) restricting the population of study to subjects of one or more specific gender groups [20,32,54], or 3) focus on HCI interventions or innovations around a gendered issue (e.g., pregnancy, gender identity and expression transitions, stereotype bias, etc.) [2,3,9].…”
Section: Gendermentioning
confidence: 99%
“…This early work identified a curious pattern that young Black and Hispanic men were the most frequent game players, despite being traditionally underrepresented in computing fields. Additional studies (DiSalvo, Crowley & Norwood, 2008;DiSalvo & Bruckman, 2010;DiSalvo, Yardi & Bruckman, 2011) about the unique gaming attitudes, play practices, and cultural values of young African American men directly shaped the initial Glitch Game Tester program. The intervention competitively engaged participants as beta-testers for forthcoming games related to their passions while learning about programming so that they could provide more actionable bug reports to the professional developers (DiSalvo et al, 2013).…”
Section: Stages Of Learning Sciences Projectsmentioning
confidence: 99%
“…In an effort to improve such low numbers, DiSalvo et al () designed a research intervention, Glitch Game Testers, involving resource‐poor 15‐year‐old Black teenagers in Atlanta. The researchers designed the intervention around a technological strength of Black males—passion for video games.…”
Section: Adult Education's Role In Helping Black Men Succeedmentioning
confidence: 99%
“…Participants were strongly motivated; they tended to arrive 30 minutes early to play games or work on programming projects. Eleven of 12 students decided to focus on computer science in college after participating in this intervention (DiSalvo et al., ).…”
Section: Adult Education's Role In Helping Black Men Succeedmentioning
confidence: 99%